(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2010)
This article argues that, even though the issue of development has a profound and far-reaching impact on human lives, sustainable development, which considers human lives for today and tomorrow has a positive impact on human development. The principal goal of this paper is to critically examine the potential role of sustainable development, a concept rooted in the eighteenth-century idea of "natural balance" or natural equilibrium in developing a human civilisation. Not unexpectedly, such a lofty, global objective has raised questions in the minds of experts used to dealing with developmental issues in a usual, compartmentalised manner. While there has been some reflection as to what constitutes sustainable development, the same cannot be said for a sustainable society. Yet sustainability is critical for all nations today and the gradual implementation of measures for sustainable development strongly reinforces the quest for a sustainable society and for the development of human civilisation.